2012
DOI: 10.1371/journal.pone.0048477
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeography of Y-Chromosome Haplogroup H1a1a-M82 Reveals the Likely Indian Origin of the European Romani Populations

Abstract: Linguistic and genetic studies on Roma populations inhabited in Europe have unequivocally traced these populations to the Indian subcontinent. However, the exact parental population group and time of the out-of-India dispersal have remained disputed. In the absence of archaeological records and with only scanty historical documentation of the Roma, comparative linguistic studies were the first to identify their Indian origin. Recently, molecular studies on the basis of disease-causing mutations and haploid DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…First, a study based on Y-chromosome haplogroups showed that on the paternal lineage, Roma haplotypes cluster predominantly with the Northwestern Indian haplotypes [26], consistent with our findings based on autosomal IBD sharing. The second study was based on whole genome SNP genotype data like ours [27].…”
Section: Discussionsupporting
confidence: 90%
“…First, a study based on Y-chromosome haplogroups showed that on the paternal lineage, Roma haplotypes cluster predominantly with the Northwestern Indian haplotypes [26], consistent with our findings based on autosomal IBD sharing. The second study was based on whole genome SNP genotype data like ours [27].…”
Section: Discussionsupporting
confidence: 90%
“…2a) appears at low levels in Iran. As an aside, the bulk of Romani lineages belongs to the branch M5a1b1a1 [70] at 3.0 ka, supporting previous linguistic and genetic evidence for a South Asian origin for the Romani diaspora [70, 71] in the west of the Subcontinent.
Fig. 2 a ADMIXTURE analysis for K  = 7. b PCA of South Asian populations.
…”
Section: Resultssupporting
confidence: 74%
“…A large number of research papers have documented mtDNA and Y-chromosome variation among Indian populations (Bamshad et al 2001;Kivisild et al 1999Kivisild et al , 2003Corduex et al 2003;Basu et al 2003;Palanichamy et al 2004;Sengupta et al 2006;Sahoo et al 2006;Gutala et al 2006;Thanseem et al 2006;Zerjal et al 2007 ;Thangaraj et al 2006a, b;Sengupta et al 2006;Chaubey et al 2008;Mittal el al. 2008;Eaaswarkhanth et al 2010;Chaubey et al 2011;Debnath et al 2011;Wang et al 2011;Rai et al 2012;Chaubey et al 2014). Barnabas et al (1996) was one of the earliest studies, using low resolution mtDNA analysis among linguistically different Indian populations to document a high level of nucleotide diversity among Indians.…”
Section: Mitochondrial and Y Chromosome Dna Markersmentioning
confidence: 99%